2009
DOI: 10.1007/s11745-009-3346-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Linseed on Intramuscular Fat Content and Adipogenesis Related Genes in Skeletal Muscle of Pigs

Abstract: The aim of the study was to investigate the effect of n-3 PUFA enrichment in longissimus muscle on intramuscular fat (IMF) content and expression of related genes in growing-finishing barrows. Two isoenergetic, isonitrogenous and isolipidic diets were formulated: one was basal diet and the other contained 10% linseed. Twenty-four Landrace x NewDamLine barrows weighing 35 +/- 3.7 kg were randomly assigned to four treatment groups with six pigs per group. During the whole experimental period of 90 days, all grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 68 publications
0
33
4
Order By: Relevance
“…Treatment E offspring had a lower IMF in the SM compared with control but had no observable difference in PPAR-g expression. This is in contrast to Luo et al (2009), who showed a positive relationship between PPAR-g and IMF in pigs using a 10% linseed diet. Instead, this study noted a decrease in PPAR-d levels in Treatment E offspring.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Treatment E offspring had a lower IMF in the SM compared with control but had no observable difference in PPAR-g expression. This is in contrast to Luo et al (2009), who showed a positive relationship between PPAR-g and IMF in pigs using a 10% linseed diet. Instead, this study noted a decrease in PPAR-d levels in Treatment E offspring.…”
Section: Discussioncontrasting
confidence: 99%
“…PPAR-d plays a role in lipid oxidation (Tanaka et al, 2003) and has also been implicated in regulating adipogenesis in mouse myoblasts (Yu et al, 2008). However, according to Luo et al (2009), PPAR-g is more closely related to IMF content than PPAR-d and in our study PPAR-g remained unchanged between treatments.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Lipids were extracted from the liver tissue samples using chloroform/methanol (1 : 1 v/v) by a modified method of Folch et al (1957). Fatty acid methyl esters were prepared for gas chromatography determination using KOH/methanol (Luo et al 2009). …”
Section: Birds Management and Experimental Designmentioning
confidence: 99%
“…Dietary fatty acids are absorbed by monogastric animals and deposited in their tissues, n-6 and n-3 PUFAs are competitively metabolized by the same pathway (Luo et al 2009). So, there is a considerable potential for the manipulation of the fatty acid profiles of poultry tissue by dietary means, thus to increase the supply of n-3 PUFA (especially EPA and DHA), and to regulate n-6/n-3 PUFA ratio to a level which is suitable for human consumption.…”
Section: Introductionmentioning
confidence: 99%